2014
DOI: 10.1111/josh.12141
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Summer Season and Body Fatness and Aerobic Fitness Among Hispanic Children

Abstract: Results indicated that the SS might place Hispanic children at increased risk for additional adiposity and lower fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…The summer weight gain phenomenon has been observed among elementary school students in a variety of geographical locations with varying climates including Japan, Minnesota, Wyoming, and Texas . The consistency of summer weight gain across elementary school students in multiple geographical climates leads us to infer that our observations among Texan middle school students are not an anomaly specific to the especially hot climate in this area during these months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The summer weight gain phenomenon has been observed among elementary school students in a variety of geographical locations with varying climates including Japan, Minnesota, Wyoming, and Texas . The consistency of summer weight gain across elementary school students in multiple geographical climates leads us to infer that our observations among Texan middle school students are not an anomaly specific to the especially hot climate in this area during these months.…”
Section: Discussionmentioning
confidence: 99%
“…Among low‐income Hispanic third‐ and fourth‐grade students aged 8 to 12 years in southeast Texas, overweight/obese students decreased their BMIs during the school year and maintained this change over the summer. On the other hand, normal weight children did not exhibit changes in BMIs during either time period …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Seasonal body mass index (BMI) growth variations with adverse summer vacation weight gain in overweight and obese children have been observed. [17][18][19] It has been suggested that the adverse summer weight gain is due to the absence from the relatively healthier environment of school-based nutritional and physical activities that occurs when children leave school for the summer vacation of traditional agrarian calendar schools. It would follow that the nonschool summer diet and relative inactivity of the home environment might allow children to gain BMI in excess of normal due to greater exposure to an obesity-prone environment outside of school.…”
mentioning
confidence: 99%
“…Most modern studies on temporal variation in children's body weight focus on differences between the summer holiday and the school year. They show that weight gain peaks during the summer holiday in overweight children but not in normal weight children (16,17). Reasons for seasonal variation in growth may be related directly or indirectly to meteorology or cultural factors.…”
mentioning
confidence: 99%